Virus de Distemper Canino: detección molecular de diferentes aislamientos provenientes de perros de la provincia de santa fe, argentina, entre los años 2000 y 2010 - Pinotti, M. (2016)
In the city of Santa Fe, Argentina, during years 2000 and 2010, 13 wild type strains of canine distemper virus were isolated. All the samples were obtained from dogs with clinical signs of disease. Isolations were performed in MDCK cells which shown characteristic cytopathogenic effect. Identification of the wild type strains was performed by RT-PCR of a region that encodes NP nucleoprotein associated to RNA. The amplified product was a 287 bp corresponding to positions 769-1055 of the Onderstepoort and Lederle vaccine strains genome, which confirmed presence of the virus in all the samples. The isolate strains were tested by neutralization on MDCK cells with the monoclonal antibody against protein H, and only 6 of them were neutralized. This finding suggests the inability of the vaccine strains to protect the canines against the circulation of some wild type strains.